Effect of increased inspired oxygen on exercise performance in patients with heart failure and normal ejection fraction. (1st October 2018) - Shah, Parin; Pellicori, Pierpaolo; Rimmer, Stella; Rigby, Alan S.; Clark, Andrew L.
Abstract: Introduction: We investigated whether increased concentrations of inspired oxygen (Fio 2 ) affects exercise tolerance in patients with heart failure and normal ejection fraction (HeFNEF). Methods: 46 patients (mean age 75 years (63% male) and median NTproBNP 1432 (interquartile range: 543–2378 ng/l)) with HeFNEF (defined as signs or symptoms of heart failure requiring treatment with diuretics, with a left ventricular ejection fraction of >45% by echocardiography and amino terminal pro brain natriuretic peptide (NTproBNP) >220 ng/l) completed three maximal incremental exercise tests with different Fio 2 (21%, 28% and 40%) in random order. Fio 2 was controlled by investigator but blinded to patients. The primary outcome was exercise time (ET). Results: Increasing Fio 2 significantly increased exercise time (522 ± 180 seconds for 21% to 543 ± 176 seconds, and 542 ± 177 seconds, for 28% and 40%, respectively, P  = 0.04) with no difference in peak workload (57 ± 25 W, 58 ± 25 W and 57 ± 25 W, for 21%, 28% and 40%, respectively, P  = 0.50). There was an increase in oxygen saturation but no change in peak heart rate with increasing Fio 2. Compared to patients with LVEF ≥50%, patients with LVEF between 45 and 49% had a significantly greater exercise time and peak workload. There was a correlation between the difference in exercise time between Fio 2 21% and 40% and age; but not with BMI, haemoglobin, creatinine or NTproBNP. Conclusion: Increasing Fio 2 during exertion leads to a small increase in exercise time in patients with HeFNEF. Highlights: The clinical hallmark of heart failure with normal ejection fraction (HeFNEF) is breathlessness. Increasing oxygen supplementation during exertion leads to a small increase in exercise time. However this is unlikely to be clinically significant in patients with HeFNEF. The mechanisms causing exercise intolerance in patients with HeFNEF are complex.